Effect of tuning capacitance of passive power repeaters on power transfer capability of inductive power transfer systems. Issue 2 (6th August 2018) - Hua, Rong; Hu, Aiguo Patrick
Abstract : Power repeaters are used to extend the power transfer range or enhance the power transfer capability of Inductive Power Transfer (IPT) systems, but how to tune the power repeaters to improve the system power transfer performance remains an unsolved problem. In this paper, studies of the effect of the tuning capacitance of the power repeater of an IPT system on the power transfer capability are presented. A theoretical model is established to analyze the output power of the system with the primary coil and secondary coil tuned at a nominal resonant frequency, and a passive power repeater placed in between. By analyzing the relationship between the tuning capacitance of the power repeater and the output power, a critical tuning capacitance which sets up the boundary between enhancing and reducing the output power is determined, and the optimal tuning capacitances corresponding to the maximum and minimum output power are also obtained. A practical IPT system with a passive power repeater placed at 40, 80, and 104 mm from the primary coil is built. It has shown that the practically measured critical capacitance and the optimal tuning capacitance for maximum power transfer are in good agreement with the analytical results.